Angular Speed Of Leading Leg During Take Off And Its Relationship With Achievement in Youth High Jumpers - Nagi, Ahmed; yusef, Radwan (Journal of Physical Education, 2017)
The Problem of the research lies in weak leading Leg swing in most high jumpers. The researcher used the descriptive method. The subjects were (7) youth high jumpers of the season 2015 from the national center for gifted in athletics. Three high quality video cameras were used to analyses movement using Kinovea program. The kinematical variables of each point of the body as well as the body center were specified. The data was collected and treated using SPSS. The researcher concluded that after analyzing angular speed of the leading leg there was weakness in the physical abilities of Iraqi high jumper that lead to humble achievements. The researcher recommended paying attention to basic analytical mechanics of angular speed and leading leg swing to develop the knowledge of local coaches and high jumper